2012
DOI: 10.15690/vramn.v67i10.413
|View full text |Cite
|
Sign up to set email alerts
|

Nad+-Converting Enzymes in Neuronal and Glial Cells: Cd38 as a Novel Target for Neuroprotection

Abstract: The review contains current data on molecular mechanisms which control NAD+ homeostasis in brain cells. It also deals with the role of NAD+-converting enzymes in regulation of functional activity, viability and intercellular communication of neuronal and glial cells. Special attention is paid to involvement of CD38 into regulation of NAD+ levels in brain cells in normal and pathological conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 64 publications
(82 reference statements)
0
3
0
4
Order By: Relevance
“…Later, it was confirmed that both the enzymes are widely expressed in the brain being predominantly found in neurons, astrocytes, and microglia (Ceni et al, 2003 ) where they take part in the action of neurotransmitters, coordinate neuron-astrocyte metabolic coupling, regulate local immune response. In particular regions of the brain (hypothalamic area and pituitary) CD38 controls NAD + metabolism and neurosecretory activity required for oxytocin secretion which regulates various neurobehavioral responses, i.e., interpersonal communications, parental behavior, decision making (Lopatina et al, 2011 , 2012 ; Higashida et al, 2012 ; Salmina et al, 2012 ; Akther et al, 2013 ). Expression of CD38 and CD157 is controlled by pro-inflammatory cytokines, retinoic acid, cell proliferation or differentiations status, and availability of their own ligand NAD + (Malavasi et al, 2008 ).…”
Section: Mechanisms and Markers Of Cell Senescence: Applications For mentioning
confidence: 99%
“…Later, it was confirmed that both the enzymes are widely expressed in the brain being predominantly found in neurons, astrocytes, and microglia (Ceni et al, 2003 ) where they take part in the action of neurotransmitters, coordinate neuron-astrocyte metabolic coupling, regulate local immune response. In particular regions of the brain (hypothalamic area and pituitary) CD38 controls NAD + metabolism and neurosecretory activity required for oxytocin secretion which regulates various neurobehavioral responses, i.e., interpersonal communications, parental behavior, decision making (Lopatina et al, 2011 , 2012 ; Higashida et al, 2012 ; Salmina et al, 2012 ; Akther et al, 2013 ). Expression of CD38 and CD157 is controlled by pro-inflammatory cytokines, retinoic acid, cell proliferation or differentiations status, and availability of their own ligand NAD + (Malavasi et al, 2008 ).…”
Section: Mechanisms and Markers Of Cell Senescence: Applications For mentioning
confidence: 99%
“…HMGB 1 нейронов участву-ют в развитии нейровоспаления после перенесенного субарахноидального кровотечения [47]. Высвобождение HMGB 1 из клеток микроглии приводит к развитию ней-ропатической боли, индуцирует апоптоз нейронов при хронической нейродегенерации, участвует в патогенезе ишемического повреждения головного мозга и аутоим-мунного воспаления [48].…”
Section: механизмы межклеточной коммуникации при воспалении и старениunclassified
“…Особенности энергетического метаболизма нейронов и астроцитов определяют их чувствительность к повреждающему действию гипоксии [26]. Считается, что астроциты -это более устойчивые к гипоксическому повреждению клетки вследствие того, что в астроцитах доминирует синтез аденозинтрифосфата (АТФ) путем гликолиза, а нейроны функционируют в основном за счет окислительного фосфорилирования в митохондриях, будучи одновременно зависимыми от поступления в них лактата из астроцитов [27].…”
Section: регуляция инсулином транспорта и метаболизма глюкозы в ткани головного мозгаunclassified